Múltiples territorios y usos de suelo en conflicto en el Partido de Esteban Echeverría. El caso de la Reserva Natural Integral y Mixta Laguna de Rocha a partir de 2012 - Alabart, Pablo (2022)
The selected topic addresses conflicting land uses in the ―LAGUNA DE ROCHA‖ natural and mixed reserve. The protected zone belongs to the AMBA (Buenos Aires Metropolitan Area), within The Matanza Riachuelo (river basin). In this area problems of housing precariousness are evident, along with the presence of other social actors that modify the territorial dynamics. The work on concepts related to territoriality from a postmodern geographical perspective. Social groups generate territories by taking possession of a certain space, where they project exchanges, relationships and generate tensions. The land becomes territory during the time that the ―appropriation‖ of the groups that are projected in the space endures, through cultural practices and symbolic projections. However, there is another form of territoriality that accompanies it. It refers to ―domination‖, and is linked to vertical interference in a given territory by the state or corporate actors. Both territorializations have temporary dependence. Consequently, the topic to be investigated, represented by phenomena of multiterritoriality within the Laguna de Rocha, Integral and Mix Nature Reserve, has the aforementioned relationships of ―appropriation and domination‖. The territoriality of two referential actors located within the protected area will be studied: Asentamiento 09 de enero (JANUARY 9th settlement) and Hogar Escuela Evita (Evita Home School). For both referential actors cultural factors of existence, lived space, appropriated and valued territory will be taken into account. In coincidence with the Declaration of the Reserve, the investigation will be from 2012 to the present. Qualitative and historicist methods will be used for the study. It will appeal to sciences such as sociology and history, along with the legal corpus that sustains the territories from a juridical basis.